Profesionalisme Pegawai Ditinjau Dari Aspek Pengorganisasian Dalam Pelayanan Publik - Abdul Wahab Podungge; Asna Aneta (Universitas Muhammadiyah Gorontalo, 2020)
This article aims to analyze: Employee professionalism in terms of organizational aspects in publik services. The method used in this article is a qualitative method. The results of the article show that the tendency of apparatus to be less professional in carrying out their duties and functions is partly due to the low motivation to make changes and innovate. The apparatus tends to be reluctant to make changes due to a lack of encouragement from the leadership. In realizing a professional, accountable, and transparent apparatus, it requires a leader role as a guide and has a visionary spirit and vision in the Gorontalo City One Stop Integrated Services and Investment Service. Concrete steps for leaders in creating a democratic climate where subordinates are included in every policy making related to improving organizational performance and building two-way communication in every activity will make subordinates feel that they are an important part of the organization. The attitude of the leader to foster a responsive spirit in every employee can improve the quality of licensing and non-licensing services in Gorontalo City. Efforts that can be made to foster the professionalism of the personnel are by making long-term, medium-term and short-term work programs and setting priority scales in every activity aimed at improving the quality of publik services.Artikel ini bertujuan untuk menganalisis tentang profesionalisme pegawai ditinjau dari aspek pengorganisasian dalam pelayanan publik. Metode yang digunakan dalam artikel ini yakni metode kualitatif. Hasil artikel menunjukan bahwa kecenderungan aparat kurang profesional dalam menjalankan tugas dan fungsinya antara lain disebabkan oleh rendahnya motivasi untuk melakukan perubahan dan berinovasi. Aparat cenderung enggan melakukan perubahan dikenakan kurangnya dorongan dari pimpinan. Dalam mewujudkan aparat yang profesional, akuntabel, dan transparan maka dibutuhkan peran pemimpin sebagai pengarah dan memiliki jiwa dan pandangan yang visioner pada Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kota Gorontalo. Langkah-langkah konkrit pemimpin dalam menciptakan iklim demokrasi dimana bawahan disertakan dalam setiap pengambilan kebijakan yang berkaitan dengan peningkatan kinerja organisasi serta membangun komunikasi dua arah dalam setiap kegiatan akan membuat bawahan merasa dirinya adalah bagian penting dalam organisasi. Sikap pemimpin untuk menumbuhkan jiwa responsif pada setiap pegawai dapat meningkatan kualitas pelayanan perizinan dan non perizinan di Kota Gorontalo. Upaya yang dapat dilakukan untuk menumbuhkan profesionalisme aparatur adalah dengan membuat program kerja jangka Panjang, jangka menengah, dan jangka pendek serta menetapkan skala prioritas dalam setiap kegiatan yang bertujuan meningkatkan kualitas pelayanan publik.